Mammalian Target of Rapamycin: Its Role in Early Neural Development and in Adult and Aged Brain Function - Garza-Lombó, Carla; Gonsebatt, María E. (Frontiers in Cellular Neuroscience, 2016)
The kinase mTOR integrates signals triggered by energy, stress, oxygen levels and growth factors. It regulates ribosome biogenesis, mRNA translation, nutrient metabolism, and autophagy. mTOR participates in various functions of the brain, such as synaptic plasticity, adult neurogenesis, memory and learning. mTOR is present during early neural development and participates in axon and dendrite development, neuron differentiation, and gliogenesis, among other processes. Furthermore, mTOR has been shown to modulate lifespan in multiple organisms. This protein is an important energy sensor that is present throughout our lifespan; its role must be precisely described in order to develop therapeutic strategies and prevent diseases of the central nervous system. The aim of this review is to present our current understanding of the functions of mTOR in neural development, the adult brain and aging.